Four little Blossoms through the holidays - Hawley, Mabel C.; Herbert, Robert Gaston, 1873-1954 (Salt Lake City, UT : Project Gutenberg, 2023)
"Four Little Blossoms Through the Holidays" by Mabel C. Hawley is a children's novel written in the early 20th century. The story follows four siblings$1 (BMeg, Bobby, Dot, and Twaddles$1 (Bas they prepare for the Thanksgiving holiday and navigate a series of amusing and heartfelt adventures centered around their charitable efforts and holiday festivities. The opening of the book introduces the Blossoms in their lively household as they excitedly prepare Thanksgiving donations for those in need. Meg is tasked with gathering supplies, while Bobby helps sort the fruits, and Dot and Twaddles are eager to contribute as well, despite their young age. Their efforts lead to charming interactions with family and friends, including humorous misunderstandings and warm-hearted moments, setting a lighthearted tone that foreshadows the delightful holiday experiences awaiting them throughout the narrative. (This is an automatically generated summary.)s
Release date is 2023-01-13
David Edwards, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Schools -- Juvenile fiction; Twins -- Juvenile fiction; Family -- Juvenile fiction; Siblings -- Juvenile fiction; Holidays -- Juvenile fiction; Thanksgiving Day -- Juvenile fiction; Christmas -- Juvenile fiction; Tramps -- Juvenile fiction; Arson -- Juvenile fiction